PENGARUH LEVERAGE DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS (ROE) PADA PERUSAHAAN PROPERTY REAL ESTATE YANG TERDAFTAR DI BEI (2014 – 2018) - Pristina Nur Andayani; Yamin Siregar; Eka Dewi Setia Tarigan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The purpose of this study was to determine the effect of leverage and company growth on profitability (ROE) in property and real estate companies listed on the IDX. This type of research is a saturated sample, which is a sampling technique that when an entire population is used as a sample. Population of this study is a total of 12 companies that contain data on financial statements of real estate property companies listed on the Stock Exchange during the 2014-2018 period. The analysis technique used is multiple linear regression analysis, namely with the help of E-views 10. In this study it is also known that DAR has a probability value of 0.2373 0.05 and the regression coefficient of the DAR variable that is equal to 0.97296 0.05 where the value indicates the DAR partially does not significantly influence the ROE variable, the probability value of the company's growth is 0.0030 0, 05 where the company growth partially has a significant effect adapts ROE variable.